Case report: early onset de novo FSGS in a child after kidney transplantation : a successful treatment - Carvajal Abreu, Karla; Loos, Sebastian; Fischer, Lutz; Pape, Lars; Wiech, Thorsten; Kemper, Markus J.; Tönshoff, Burkhard; Oh, Jun; Schild, Raphael-Sebastian (Frontiers in Pediatrics, 2023)
BackgroundEarly onset de novo focal segmental glomerular sclerosis (FSGS) in the kidney allograft in patients without FSGS in the native kidney is a rare disorder in children. It usually occurs mostly beyond the first year after kidney transplantation and often leads to graft loss. Standardized treatment protocols have not yet been established.Case descriptionWe describe a boy with early onset de novo FSGS in the transplanted kidney and non-selective glomerular proteinuria (maximum albumin-to-creatinine ratio of 3.8 g/g; normal range, ≤0.03 g/g creatinine). Manifestation occurred at 30 days posttransplant and was accompanied by a significant graft dysfunction (eGFR 61 ml/min per 1.73 m2). Treatment with 25 sessions of plasmapheresis over 14 weeks and three consecutive days of methylprednisolone pulse therapy (10 mg/kg per day) followed by oral prednisolone as rejection prophylaxis (3.73 mg/m2 per day) led to sustained remission of proteinuria (albumin-to-creatinine ratio of 0.028 g/g) and normalization of graft function (eGFR 92 ml/min per 1.73 m2) after 14 weeks. The follow-up period was 36 months.ConclusionsThis case underlines the efficacy of immunosuppressive and antibody eliminating therapy in early onset de novo FSGS after kidney transplantation.